Women’s Role in Jeju Society through the Character of Oh Ae-sun In When Life Gives You Tangerines - Kartika Aprilia Siagian; Pratiwi Retnaningdyah (CV. Ulil Albab Corp, 2026)
Women's roles in patriarchal societies highlight domestic tasks, caregiving duties, and submission, guiding women to value family needs over their own liberty. This research investigates how women's roles are portrayed and negotiated within modern Korean culture. This study draws on Simone de Beauvoir's existential feminism (1949) to examine women's roles in the Netflix series When Life Gives You Tangerines (2025), a Korean drama. On Jeju Island, the drama portrays Oh Ae-sun navigating the roles of mother, wife, and worker in a patriarchal tradition-filled society. Through textual analysis, the research targets chosen moments that feature patriarchal standards, role tensions, and women's opposition. The work reveals Ae-sun taking mother, wife, and worker roles, all crafted by patriarchal values limiting her to immanence through sacrifice, submission, and endless labor. Ae-sun's figure brings out resistance, leadership, and creative expression as steps to transcendence. Findings indicate that Jeju patriarchal structures limit women's self-determination, yet Ae-sun goes on negotiating her identity within those bounds. The research adds to feminist literary criticism by bringing existential feminism to a modern Korean TV narrative from a rural locale largely ignored in scholarship.